Elderly people and ulcer caused by pressure at home care service - Coêlho, Ana Débora Alcantara; Lopes, Marcos Venícios de Oliveira; Melo, Renata Pereira de; Castro, Maria Euridéa de (Rev Rene, 2012)
This research aimed at estimating the prevalence of pressure ulcers in a home care service. Cross-sectional study carried out in July/August 2009 with 194 bedridden aged patients. For data collection, the Braden Scale and an instrument consisting of demographics, clinical data, and preventive measures for pressure ulcers were applied. Data was analyzed using SPSS16.0 and presented as descriptive statistics. From the total sample, 69.6% (n = 135) were female; 68% (n = 132) ≥ 80 years old; 33% (n=64) were Alzheimer patients, and 26.3% (n = 51) had sequels of stroke; 31.4% (n = 61) had pressure ulcers, from which 54.1% (n = 33) were developed in the hospital. A prevalence of 31.4% and moderate risk (13.2%) for pressure ulcers was identified. It is recommended longitudinal study for evaluating the relationship between the Braden Scale indicators and the development of pressure ulcers.